Cuidado familiar após infarto agudo do miocárdio - Garcia, Raquel Pötter (2013)
The cardiovascular diseases compose relevant situations of disabilities and deaths worldwide. The Acute Myocardial Infarction (AMI) is characterized as a complication of the Coronary Artery Disease, which is the most frequent form of the chronic atherosclerotic disease. Thus, the AMI is an acute manifestation of a chronic disease. The heart illness may trigger in the patient as well as in the family a considerable emotional suffering, as everyone is affected and the family dynamics is changed in order to find a balance. When visualizing the family as a unit, it is possible to detect the interactions between its members and understand its cares and the way it works concerning the disease. This study had as its general purpose understanding how the family care develops after an AMI event in one of its members. And as specific purposes: describe the immediate and current experiences faced by the family after an AMI; know about the care developed by the patient s families after an AMI; and know about the social support the family receives concerning the care necessity after an AMI. It is an exploratory, descriptive, qualitative, field research, carried out with six families of post AMI patients. The data collection took place between February to May 2012 and it was held through observation sessions at the Cardiology Ambulatory and at the patient s residences, as well as through interviews with the families. Such interview was composed by a genogram construction and a family ecomap, as well as questions previously planned in a guide. The field journal was used to register the researcher s perceptions and observations. In order to help in the coding of the interviews, the software Atlas Ti 6.2 was used, and the data go through thematic analysis. The research met the ethical principles of the Resolution n. 196/96 and was approved by the Ethics Committee under the n. 0372.0.243.000-11. The results are presented in the article format: Article 1: Family experiences after acute myocardial infarction; Article 2: Family care after an acute myocardial infarction: implications for nursing; Article 3: Family social support concerning the necessity of care after myocardial infarction. The understanding of the families experiences after the AMI helps approaching the context and appropriate care, which enables affirming that the family care, concerning the AMI, depends on the phase of the disease which the family is facing, in which some moments such care more intense and in others it is less. Besides that, within the family, it was possible to find different ways of care which keep the family in a constant attempt to keep the balance. To have this care given, it is also necessary the support of other systems, besides the family, such as neighbors, friends and professionals. Thus, it concerns the Nursing field to more effectively take part in the life of the individuals and their families, through the use of health promotion and prevention activities, as the families pointed out the use of immediate assistance practices concerning only questions related to hospitalization.